2014
DOI: 10.1501/vetfak_0000002645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat conditioning and dietary ascorbic acid supplementation on growth performance, carcass and meat quality characteristics in heat-stressed broilers

Abstract: Summary:This study was conducted to investigate the effects of heat conditioning and dietary ascorbic acid supplementation on growth performance, carcass and meat quality characteristics in heat-stressed broilers. A total of 320 male broilers were randomly assigned to 4 treatment groups as positive control (PC), heat stress (HS), heat conditioning (HC) and ascorbic acid supplementation (AA). Broilers in PC group were housed in thermoneutral conditions (24 o C) and fed with the basal diet throughout experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
5
12
2
3
Order By: Relevance
“…Statistical significance was observed compared to other groups, but without difference in feed conversion when compared to the control group in the end. These results are not compatible with the results obtained by Oral Toplu et al [22], who concluded that Vit C stimulated feed conversion in broilers bred in HS conditions. Different results may be due to dosages of Vit C, which were different, as well as to the manner in which this supplement was administered.…”
Section: Growth Performancescontrasting
confidence: 99%
See 3 more Smart Citations
“…Statistical significance was observed compared to other groups, but without difference in feed conversion when compared to the control group in the end. These results are not compatible with the results obtained by Oral Toplu et al [22], who concluded that Vit C stimulated feed conversion in broilers bred in HS conditions. Different results may be due to dosages of Vit C, which were different, as well as to the manner in which this supplement was administered.…”
Section: Growth Performancescontrasting
confidence: 99%
“…Group TC had the largest volume of carcass (grill chicken) (69.25%) when compared to other groups; when compared to group K specifically (66.43%), a statistical difference was obtained. Oral Toplu et al [22] concluded that in HS conditions there were larger percentages of carcass (grill chicken) in broilers supplemented with Vit C or exposed to ETC when compared to a group which did not undergo this kind of treatment, which is in accordance with our results. This research did not include a combination of Vit C and ETC, which led to the best results in our case with statistical difference.…”
Section: Carcass Traitssupporting
confidence: 92%
See 2 more Smart Citations
“…pH sangat mempengaruhi kualitas daging, karena nilai pH adalah refleksi langsung dari kandungan asam otot, dan mempengaruhi keempukan, daya ikat air dan warna daging (Toplu et al, 2014). Pada penelitian ini perbedaan suhu pemeliharaan memberikan pengaruh nyata terhadap nilai pH daging ayam broiler dimana pada pemeliharaan suhu lingkungan yang tinggi (35-36ºC) memiliki pH lebih rendah (asam).…”
Section: Pendahuluanunclassified